Enhanced Charge Separation through ALD‐Modified Fe2O3/Fe2TiO5 Nanorod Heterojunction for Photoelectrochemical Water Oxidation. Issue 25 (19th May 2016) - Li, Chengcheng; Wang, Tuo; Luo, Zhibin; Liu, Shanshan; Gong, Jinlong
Abstract : Hematite suffers from poor charge transport and separation properties for solar water splitting. This paper describes the design and fabrication of a 3D Fe2 O3 /Fe2 TiO5 heterojunction photoanode with improved charge separation, via a facile hydrothermal method followed by atomic layer deposition and air annealing. A highly crystallized Fe2 TiO5 phase forms with a distinct interface with the underlying Fe2 O3 core, where a 4 nm Fe2 TiO5 overlayer leads to the best photoelectrochemical performance. The favorable band offset between Fe2 O3 and Fe2 TiO5 establishes a type‐II heterojunction at the Fe2 O3 /Fe2 TiO5 interface, which drives electron–hole separation effectively. The Fe2 O3 /Fe2 TiO5 composite electrode exhibits a dramatically improved photocurrent of 1.63 mA cm −2 at 1.23 V versus reversible hydrogen electrode (RHE) under simulated 1 sun illumination (100 mW cm −2 ), which is 3.5 times that of the bare Fe2 O3 electrode. Decorating the Fe2 O3 /Fe2 TiO5 heterojunction photoanode with earth‐abundant FeNiO x cocatalyst further expedites surface reaction kinetics, leading to an onset potential of 0.8 V versus RHE with a photocurrent of 2.7 mA cm −2 at 1.23 V and 4.6 mA cm −2 at 1.6 V versus RHE. This sandwich photoanode shows an excellent stability for 5 h and achieves an overall Faradaic efficiency of 95% for O2 generation. This is the best performance ever reported for Fe2 O3 /Fe2 TiO5 photoanodes. Abstract : Fe2 O3 /Fe2 TiO5 nanorod (NR) photoanode is prepared by coating TiO2 thin film over hydrothermal FeOOH NRs through atomic layer deposition (ALD), followed by a post‐annealing process. The formed heterojunction at the surface greatly enhances the separation of photo‐carriers and consequently improves the photoelectrochemical water oxidation efficiency. This constitution demonstrates the advantages of ALD in surface modification and the importance of well‐organized heterojunction photoelectrode for water splitting.